The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/2470547016688693
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Confinement Stress-induced Hypothalamic-pituitary Adrenal Axis Activation and Concomitant Peripheral and Central Transforming Growth Factor-β1 Measures in Nonhuman Primates

Abstract: Transforming growth factor-β1 (TGF-β1) is a multifunctional cytokine with anti-inflammatory, immunosuppressive and neuroprotective properties. The hypothalamic-pituitary-adrenal (HPA) axis and immune system exert bidirectional influences on each other, via cortisol and TGF-β1, but the exact nature of the interaction is not well characterized. The current study examined the effects, in bonnet macaques (Macaca radiata), of two consecutive acute confinement stress periods in an unfamiliar room while mildly restra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“… Li et al [ 165 ]: provides robust ischemic neuroprotection but also exerts neurotoxicity when administered during ischemia and early reperfusion. 60 Dexamethasone Synthetic steroid Coplan et al [ 166 ]: glucocorticoid-induced neurotoxicity. Yu et al .…”
Section: Resultsmentioning
confidence: 99%
“… Li et al [ 165 ]: provides robust ischemic neuroprotection but also exerts neurotoxicity when administered during ischemia and early reperfusion. 60 Dexamethasone Synthetic steroid Coplan et al [ 166 ]: glucocorticoid-induced neurotoxicity. Yu et al .…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that no correlation exists between a central deficit of TGF-β1 after PNS procedure and the reduced levels of this cytokine in the periphery. A recent study conducted in non-human primates, exposed to two consecutive acute confinement stress periods, seems to suggest this hypothesis, with the stress condition able to decrease TGF-β1 concentrations only in cerebrospinal fluid, but not in serum (Coplan et al, 2017).…”
Section: Molecular Mechanisms Underlying Vulnerability To Depression ...mentioning
confidence: 99%
“…In this context, the confinement of the population caused by COVID-19 is considered a cause that has led to stress states and consequent diminishing of the neurogenesis process, especially in vulnerable subjects, as demonstrated in studies carried out on nonhuman animals. Thus, Coplan et al indicate that acute confinement of primates tends to promote states of depression and anxiety that correlate with elevated cortisol levels. Furthermore, other authors have indicated the monitoring of important biomarkers which have been used to screen drugs and bioactive compounds with antidepressant potential. …”
Section: Introductionmentioning
confidence: 99%